Potential Utility of Systemic Plasma Biomarkers for Evaluation of Pediatric Schistosomiasis in Western Kenya - Ondigo, Bartholomew N.; Hamilton, Rachael E.; Magomere, Edwin O.; Onkanga, Isaac O.; Mwinzi, Pauline N.; Odiere, Maurice R.; Ganley-Leal, Lisa (Frontiers in Immunology, 2022)
Introduction: Current diagnostic tools for schistosomiasis are limited, and new tests are necessary to enhance disease diagnosis and surveillance. Identification of novel disease-specific biomarkers may facilitate the development of such tests. We evaluated a panel of biomarkers used in sepsis and parasitic diseases for their potential suitability in diagnosis of schistosomiasis. Objective: The study evaluated the levels of systemic serum biomarkers in relation to Schistosoma mansoni infection and parasite burden. Methods: Six biomarkers were measured in plasma of children from schistosomiasis-endemic region using ELISA. The concentration of soluble CD23 (sCD23) and lipopolysaccharide (LPS) were tested in 199 and 124 plasma samples respectively, while interleukin-6 (IL-6), soluble Triggering Receptor Expressed on Myeloid (sTREM) cells, eotaxin-1, Fatty Acid Binding Protein (FABP) concentrations were tested in 30 plasma samples. Results: The concentration of interleukin-6 (IL-6), eotaxin-1, FABP and LPS were similar between schistosome-infected and uninfected children. The schistosome-infected children had higher median levels of sTREM and sCD23 compared to uninfected children, 119.0 (29.9 – 208.9) versus 10.7 (0.0 – 73.4) (p = 0.046) and 2549.0 (1899.0 – 3356.0) vs. 2035.0 (1448.0 – 2939.0) (p = 0.05) respectively. In addition, sTREM was positively correlated with egg density (p= 0.017). Conclusion: Our data show that active schistosomiasis per se is associated with elevated levels of sTREM and sCD23. sTREM has potential diagnostic and prognostic value. However, these biomarkers did not distinguish between children with low egg burden and uninfected children.